Análisis del bulevar de la avenida Naciones Unidas como espacio de promoción social, cultural y comunicacional - Baldeón Aldás, Nicole Estefanía (2016)
To achieve this research, there was the need for an investigation of the current situation in which the subject is performed. Therefore finding books and articles written by different authors who know in depth the issue of boulevards, public spaces, cities, art and more than anything as advertising has had to change to give consumers better links with the brand based on experiential campaigns. The purpose of the following study is to give brands and art an opportunity to have a presence in an important and busy public space which is the Naciones Unidas Boulevard. At the same refocusing the boulevard so you can increase tourism in the city of Quito and achieve for it to improved and promote a better way to for the social, cultural and communications field. After a field investigation was conducted. Based on the problem in general and proposed two types of research objectives, qualitative, like interviews and quantitative surveys that are developed. This study was very important as this became known what is the point of view of the professionals in advertising, art, public spaces and also involved the people in general who would become consumers. Based on the above it said it could conduct an analysis of the results obtained. The importance of this analysis is that not only found several important points to note, but managed to meet the proposed objectives. Finally it came to the part of conclusions and recommendations that should be used for the purpose of this studyand that which should be applied in the best way.